2018
DOI: 10.1142/s1793545818500359
|View full text |Cite
|
Sign up to set email alerts
|

Power spectral density-based nearinfrared sub-band detection for noninvasive blood glucose prediction in both in-vitro and in-vivo studies

Abstract: Diabetes is a widespread and serious disease and noninvasive measurement has been in high demand. To address this problem, a power spectral density-based method was offered for determining glucose sensitive sub-bands in the nearinfrared (NIR) spectrum. The experiments were conducted using phantoms of different optical properties in-vitro conditions. The optical bands 1200–1300[Formula: see text]nm and 2100–2200[Formula: see text]nm were found feasible for measuring blood glucose. After that, a photoplethysmogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Optical methods are cost-effective and sensitive for biological detections, and several strategies have been developed for optical glucose sensing and imaging. Shibata et al developed an implantable hydrogel platform based on diboronic acid and a fluorescent dye, which was further immobilized subcutaneously for in vivo continuous glucose monitoring. , Recently, Maric et al reported a bioluminescent probe that can accurately measure glucose uptake in living cells and living mice . The bioluminescent probe in tumor xenograft models exhibited high sensitivity that was comparable to the that of the 18 F-FDG tracer.…”
Section: Introductionmentioning
confidence: 99%
“…Optical methods are cost-effective and sensitive for biological detections, and several strategies have been developed for optical glucose sensing and imaging. Shibata et al developed an implantable hydrogel platform based on diboronic acid and a fluorescent dye, which was further immobilized subcutaneously for in vivo continuous glucose monitoring. , Recently, Maric et al reported a bioluminescent probe that can accurately measure glucose uptake in living cells and living mice . The bioluminescent probe in tumor xenograft models exhibited high sensitivity that was comparable to the that of the 18 F-FDG tracer.…”
Section: Introductionmentioning
confidence: 99%
“…There is a great deal of recent interest in the development of optical sensors for in vivo glucose monitoring, which can achieve a long-term operation as compared to electrochemical devices. One optical approach was developed by adopting fluorescent dye with a phenylboronic acid group, which reversibly interacts with glucose molecules to modulate the fluorescence intensity. Hydrogel microbeads and fibers consisting of the dye-phenylboronic acid were investigated for the transdermal detection of glucose. ,,, In alternative strategies, glucose oxidase was used as the recognition unit in an enzyme-based system, where the changes in pH, H 2 O 2 , or oxygen concentrations were measured for glucose concentrations . We recently demonstrate the implantable Pdot transducer for sensitive and real-time dynamic monitoring of glucose in animals. , The high brightness and ratiometric luminescence response of Pdots enabled transdermal detection via a small-phone-based imaging method .…”
mentioning
confidence: 99%